THAI MODERN MUSIC INDUSTRIAL ANALYSIS USING CULTURAL INDUSTRY CONCEPT - Punpong, Akkarong (Life Sciences and Environment Journal, 2017)
The purpose of this article was to study Thai songs production as the business via cultural industry perspective. It was clear that current Thai song industry was different from those in the past because of the technological change, particularly online media that played more roles in information consumption as well as music listening pattern in society. Therefore, the song industry needed an adjustment to survive. Such as, providing complete song service, digital service and organizing showbiz (concert). Regarding cultural industry perspective, the author concluded in two aspects. The first aspect was Adorno’s perspective. He considered Thailand social structure relied on capitalistic economy mechanism. Therefore, The Thai song industry needed to be remained in order to transform song culture into income. As a result, reproduction and copying were produced. The second aspect was Benjamin’s perspective. There was similar point to Adorno’s perspective, the songs were the outputs of cultural industry that transformed into the products. However, technological development turned the consumers as the active consumers, who were able to choose whether or not they would like to listen to the songs that were the output of market mechanism without the force from others or losing their identity.